Association between Age, Weight, and Dose and Clinical Response to Probiotics in Children with Acute Gastroenteritis. Issue 1 (3rd December 2020) - Schnadower, David; Sapien, Robert E; Casper, T Charles; Vance, Cheryl; Tarr, Phillip I; O'Connell, Karen J; Levine, Adam C; Roskind, Cindy G; Rogers, Alexander J; Bhatt, Seema R; Mahajan, Prashant; Powell, Elizabeth C; et al.
ABSTRACT: Background: Gastroenteritis is a common and impactful disease in childhood. Probiotics are often used to treat acute gastroenteritis (AGE); however, in a large multicenter randomized controlled trial (RCT) in 971 children, Lactobacillus rhamnosus GG (LGG) was no better than placebo in improving patient outcomes. Objectives: We sought to determine whether the effect of LGG is associated with age, weight z score and weight percentile adjusted for age and sex, or dose per kilogram administered. Methods: This was a preplanned secondary analysis of a multicenter double-blind RCT of LGG 1 × 10 10 CFU twice daily for 5 d or placebo in children 3–48 mo of age with AGE. Our primary outcome was moderate to severe gastroenteritis. Secondary outcomes included diarrhea and vomiting frequency and duration, chronic diarrhea, and side effects. We used multivariable linear and nonlinear models testing for interaction effects to assess outcomes by age, weight z score and weight percentile adjusted for age and sex, and dose per kilogram of LGG received. Results: A total of 813 children (84%) were included in the analysis; 413 received placebo and 400 LGG. Baseline characteristics were similar between treatment groups. There were no differential interaction effects across ranges of age ( P -interaction = 0.32), adjusted weight z score ( P -interaction = 0.43), adjusted weight percentile ( P -interaction = 0.45), or dose per kilogram of LGG received ( P -interaction = 0.28) for the primary outcome. Whereas we found a statistical association favoring placebo at the extremes of adjusted weight z scores for the number of vomiting episodes ( P -interaction = 0.02) and vomiting duration ( P -interaction = 0.0475), there were no statistically significant differences in other secondary outcome measures (all P- interactions > 0.05). Conclusions: LGG does not improve outcomes in children with AGE regardless of the age, adjusted weight z score, and adjusted weight percentile of participants, or the probiotic dose per kilogram received. These results further strengthen the conclusions of low risk of bias clinical trials which demonstrate that LGG provides no clinical benefit in children with AGE. This trial was registered at clinicaltrials.gov as NCT01773967.